Implementation of Information Technology in Improving Cooperative Management Efficiency - Felicia Zhafira Herlambang; Vera Maria; Elsanty Mulyasmi (Contemporary Journal of Applied Sciences, 2024)
In the current era of globalization, technological advances have made business activities such as cooperative management which includes planning, organizing, directing, and controlling resources and activities in cooperatives to achieve goals easier to carry out. This research methodology relies on theoretical and conceptual knowledge, and uses the research concept of literature study, which is the collection of information by browsing and understanding books, journals, articles, scientific works, and other sources of written documents, to explore the relationship between information technology and cooperative management. The primary goal of this journal is to assess the effectiveness of using information technology in managing cooperatives